THE WORK SPIRIT OF MEDIATOR EMPLOYEES: THE INFLUENCE OF COMPENSATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF EMPLOYEES AT NUSANTARA LOGISTICS HIGHER EDUCATION - Hermawati, Adya; Rosita, Ratih; Fatmawati, Endang; Nasrul, Herni Widiyah; Wibowo, Teguh Setiawan; Ali, Shujahat (Universitas Brawijaya, Indonesia, 2023)
The aim of this study is to examine the influence of compensation and work environment on employee performance through employee work spirit. The sampling technique used in this research is purposive sampling, with 46 respondents from the Head of Department (Kabag) along with the Head of Subdivision (Kasubbag) and their staff, based on the employees' minimum educational level of grade II. This research was conducted at Nusantara Logistics Higher Education located at Jl. Sari Asih No.54, Sarijadi, Sukasari District, Kudus City, Central Java. The analytical tool used is path analysis. The results of this study indicate that compensation and work environment contribute to the improvement of employee work spirit and performance, and work spirit contributes to the improvement of employee performance. Work spirit is able to mediate the influence of compensation and work environment on the improvement of employee performance. Based on the research findings, it is recommended for the leaders of Nusantara Logistics Higher Education to provide fair compensation to employees, and employees should maintain a comfortable and conducive work environment to stimulate work spirit and impact on performance improvement.